2014
DOI: 10.1080/15438627.2014.948624
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Environmental Conditions on the Decision-making Performance of Soccer Goal Line Officials

Abstract: Goal line officials (GLO) are exposed to extreme environmental conditions when employed to officiate in professional European soccer cup competitions. The present study aimed to investigate the effect of such environments on GLO decision-making ability. Thirteen male participants were exposed to three conditions: cold (-5°C, 50% relative humidity (RH)); temperate (18°C, 50% RH); and hot (30°C, 50% RH) for 90 min per condition, with a 15 min half-time break after 45 min. Decision-making ability was assessed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 14 publications
2
30
1
2
Order By: Relevance
“…Cognitive performance was improved with elevations in MST and TS after exercise, and was impaired during REST and POST-EX with decreased MST and TS in COLD. Our findings are in line with Palinkas et al (2005) and Mäkinen et al (2006), and are partly in consistent with results from Watkins et al (2014) which indicated significant correlations between MST and cognitive performance in cold (-5°C), temperate (18°C) and hot (30°C) conditions, but failed to find any correlation between TS and cognitive performance. The disassociation in their study is likely to be caused by the experimental protocol, since they administrated a 15-min break period in a thermoneutral environment halfway in the experimental session, which may result in different changes in MST and TS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cognitive performance was improved with elevations in MST and TS after exercise, and was impaired during REST and POST-EX with decreased MST and TS in COLD. Our findings are in line with Palinkas et al (2005) and Mäkinen et al (2006), and are partly in consistent with results from Watkins et al (2014) which indicated significant correlations between MST and cognitive performance in cold (-5°C), temperate (18°C) and hot (30°C) conditions, but failed to find any correlation between TS and cognitive performance. The disassociation in their study is likely to be caused by the experimental protocol, since they administrated a 15-min break period in a thermoneutral environment halfway in the experimental session, which may result in different changes in MST and TS.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies conducted in cold and temperate environments also presented a correlation between cognitive performance and subject’s Mean skin temperature (MST) and thermal sensation (TS) when subjects were seated or performing small body movements (Palinkas et al, 2005; Mäkinen et al, 2006; Watkins et al, 2014). Human and animal studies have suggested that significant reduction in body temperature would cause decline in cerebral blood flow and cerebral oxygen consumption (Laptook et al, 2001; Pozos and Danzl, 2001; Li et al, 2009), which would cause cognitive deficits (Raichle et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…No que refere aos fatores externos, verificou-se que a quantidade de torcida no estádio, sua proximidade do campo e também o local da partida e sua temperatura condicionaram de forma significativa as decisões dos árbitros, implicando em maior quantidade de cartões para a equipe visitante e uma melhor temperatura ambiental para a tomada de decisão mais assertiva (20,25,57) . No que concerne aos fatores internos, verificou-se que os árbitros assistentes possuem uma limitação ótica de projeção da imagem na retina quando a movimentação é feita em diferentes terços do campo, implicando em marcações adequadas ou não do impedimento (34) .…”
Section: Avaliações In Vivounclassified
“…No que refere aos fatores externos, verificou-se que a quantidade de torcida no estádio, sua proximidade do campo e também o local da partida e sua temperatura condicionaram de forma significativa as decisões dos árbitros, implicando em maior quantidade de cartões para a equipe visitante e uma melhor temperatura ambiental para a tomada de decisão mais assertiva (20,25,57) . No que concerne aos fatores internos, verificou-se que os árbitros assistentes possuem uma limitação ótica de projeção da imagem na retina quando a movimentação é feita em diferentes terços do campo, implicando em marcações adequadas ou não do impedimento (34) .…”
Section: Avaliações In Vivounclassified